Schizophrenia Patient’s Need Assessment - Windy Tiandini; dr. Khairina (Jurnal Psikiatri Surabaya, 2020)
Schizophrenia is a chronic mental illness and cause dysfunction in the social, work and family environment. The main goal of the treatment of schizophrenia is recovery that is either physically or mentally completed from loss of symptoms, work function, independent life, and relationships that require the role of the patient and caregiver. Planning therapy for schizophrenic patients is not just medical approval or treatment, but the discussion of basic needs is very important in order to reduce dysfunction in schizophrenic patients and improve their quality of life. The Camberwell Assessment of Need (CAN) is an instrument developed to support several aspects of life and mental well-being and to provide an overview of the needs of schizophrenic patients.